Trending in multidisciplinary research for stroke disease management - Sowtali, Siti Noorkhairina (MEDWIN Publishers, 2017)
Stroke is a clinical syndrome characterized by rapidly developing clinical symptoms and/or signs of focal, and at times global, loss of cerebral function, with symptoms lasting more than 24 hours or leading to death, with no apparent cause other than that of vascular origin according to World Health Organization definition. Currently, stroke is ranked at number five killers among Malaysian population as reported by the Ministry of Health (MOH). Thus, this mini review paper will highlight the trending in multidisciplinary research for stroke disease management throughout the different era. This is an important aspect to be understood further to fill in the knowledge gap for current research needs.